Al2O3-ZrO2 nanocomposites coating on aluminum alloy by plasma electrolytic-electrophoretic hybrid process. (June 2019) - Barati, Nastaran; Meletis, Efstathios I.
Graphical abstract: Highlights: Al2 O3 -ZrO2 nanocomposites coated on Al by plasma electrolytic hybrid process. Correlation between voltage-time response and various coating stages studied. Optical spectroscopy revealed ions involvement mechanism in coating process. HR-TEM studies showed formation of various sub-layers throughout coating. Mechanism of composite formation by hybrid plasma electrolytic discussed. Abstract: Alumina-zirconia nanostructured layers were coated on an aluminum alloy (AA7075) by the plasma electrolytic (PE) technique in a direct current galvanostatic mode at 0.1–0.4 A/cm 2 current density. The coatings were formed in an electrolyte containing monoclinic nano-ZrO2 powder as a zirconia source. The microstructure of the produced coatings was studied by transmission electron microscopy (TEM), scanning electron microscopy and X-ray diffraction to develop an understanding of the growth mechanism. The investigation of the coating process was complemented with voltage-time response measurements and in-situ optical spectroscopy observations. The results showed formation of various alumina-zirconia composite microstructures as a function of the current density during processing. At the higher current density, the composite layer consists of high temperature phases (tetragonal zirconia and α-alumina) in addition to monoclinic zirconia. High current density introduced larger amounts of zirconia to the coated layer due to the high energy applied to the nanoparticles in the electrolyte. TEM analysis showed formation of four sub-layers across the coating. The coating-substrate interface (sub-layer 1) contained higher amounts of alumina (both α and γ) while the amount of zirconia nanoparticles increased by moving toward the outer surface. In sub-layer 2, formation of tetragonal zirconia was observed resulting from a phase transformation of monoclinic to tetragonal zirconia. In sub-layer 3, the existence of untransformed monoclinic zirconia hints to inadequate energy for the phase transformation due to lower temperatures. At the top region of the coating, sub-layer 4, a shallow amorphous layer was formed due to quenching from the direct contact with the electrolyte. The PE process was found to be responsible for the monoclinic to tetragonal zirconia transformation, while the electrophoretic process facilitated the deposition of the original monoclinic zirconia from the electrolyte. The results showed that the coating mechanism involves a hybrid PE-electrophoretic process.